Del maltrato al uxoricidio. La violencia “puertas adentro” en la aldea chilena tradicional (siglo XIX) - Salinas Meza, René (Revista de Historia Social y de las Mentalidades, 2025)
This item manifest chilean womenfrom XIX century village were several fisical and psychological, direct and indirect, aggression victims.The aggressor Ìs violent behavior are explained by recognition as habitual actions of a daily routine; so, specifical spaces are marked in which people`s relationships, such as, the village urban world and the domestic ones are developed, in both worlds, people built jointly and fraternity collective webs, but at the same time, they develope competion Ìs relationships that produce close contacts and aggressions which show the sociability and tie.The attacked women confused the aggression and the male authority acceptance, what suposes an existance of a social and daily correct marriage. The feminine revelious attitud comfront to the social reject and the marital power shown, like aggressive con  ducts. So, the couple relationships weren Ìt among evens, instead hierarchy imposing a dependance and subordinate rol to the women, which permit men had enough authority to control and punish women. Helped by a several documental judiciary files, we try to understand and explain men and women inside familiar relations developed in chilean villages in XIX century